Hypothyroidism is Not Associated with Keratoconus Disease: Analysis of 626 Subjects - Zsuzsa Flaskó; Elena Zemova; Timo Eppig; László Módis; Achim Langenbucher; Stefan Wagenpfeil; Berthold Seitz; Nóra Szentmáry (Journal of Ophthalmology)
Purpose. To analyze the association between hypothyroidism and keratoconus, we examined blood thyroid hormone levels and corneal tomographic parameters in healthy subjects and patients with keratoconus. Methods. We included 626 subjects (304 left eyes, 49%; 431 males, 69%; age 38.4 ± 14.3 y). Patients with keratoconus were from our Homburg Keratoconus Center (HKC) (n = 463); patients with hypothyroidism were from the Department of Internal Medicine of Saarland Medical University, Homburg/Saar, Germany (n = 75); and healthy subjects were from the Department of Ophthalmology of Saarland University Medical Center (n = 88). We included only one randomly selected eye of each subject and the first examination data. Exclusion criteria. Previous thyroid medication, previous ocular surgery, and patients with suspected keratoconus (topographic keratoconus classification, [TKC]: 0 < 1). Patient eyes were classified (TKC) with dedicated, instrument-based, keratoconus detection software provided with the Pentacam. TKC = 0 was considered “normal,” and TKCs ≥ 1 were considered keratoconus. Subjects were also classified as euthyroid or hypothyroid, based on blood thyroid hormone status (i.e., TSH, FT3, and FT4). A multiple logistic linear regression model was constructed to determine the effects of age (covariate), gender, and hypothyroidism (effect sizes) on “TKC-positive” disease. Results. The significance levels for a constant parameter, sex, thyroid condition, and age were p<0.0001, p<0.0001, p<0.0001, and p=0.003, respectively. The odds ratios for age, sex, and hypothyroidism were 0.98, 3.05, and 3.34, respectively. Male sex and a euthyroid condition had significantly positive, clinically relevant effects, and age had a significantly negative, but clinically irrelevant effect on the estimated TKC index. Conclusions. Keratoconus appeared to occur more often in patients classified as euthyroid than in patients with hypothyroidism. Thus, hypothyroidism alone could not support the development of keratoconus. Based on these results, it should not be mandatory to screen patients with hypothyroidism for keratoconus or patients with keratoconus for hypothyroidism.